2017
DOI: 10.1177/1010428317691678
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223-3p inhibits human bladder cancer cell migration and invasion

Abstract: The regulation of initiation and progression during carcinogenesis of bladder carcinoma is not completely elucidated. Dysregulation of microRNAs has been detected to play critical roles in the development of various cancers, including bladder carcinoma, whereas the involvement of miR-223-3p in the tumorigenesis of bladder carcinoma has not been studied. Here, we show that significantly higher levels of nuclear receptor coactivator 1 and significantly lower levels of miR-223-3p were detected in bladder carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…Usually, miR-223 was considered to be a suppressor in multiple cancers, such as cervical cancer [28], bladder cancer [29], prostate cancer [30] and breast cancer [31]. Our results were consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 83%
“…Usually, miR-223 was considered to be a suppressor in multiple cancers, such as cervical cancer [28], bladder cancer [29], prostate cancer [30] and breast cancer [31]. Our results were consistent with these previous findings.…”
Section: Discussionsupporting
confidence: 83%
“…miRNAs are also involved in modulating different cancer-related biological processes, such as cell proliferation, cycle, apoptosis, angiogenesis, invasion, migration and metastasis (12)(13)(14). Moreover, numerous miRNAs are aberrantly expressed in various kinds of human cancers, such as EOC (15), cervical cancer (16), gastric cancer (17), lung cancer (18) and bladder cancer (19). miRNAs may act as either oncogenes or tumor suppressors in tumor initiation and progression on the basis of the biological roles of their target genes (20).…”
Section: Microrna-455 Inhibits Cell Proliferation and Invasion Of Epimentioning
confidence: 99%
“…Besides genetic variations, post-transcriptional regulations also affected the functioning of associated enzymes. For instance, NCOA1 was confirmed as a target of miR-223-3p and demonstrated to have low expression levels (53,54). Evidence has indicated that changes to the microenvironment resulting from hypoxia, which is insufficient to maintain cellular function, were associated with cancer pathology.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%